1-4-2: Evaluation of applied mechanical power to individual lungs in a simulator-based setting of one ventilator for two patients - Lars-Olav Harnisch; Christian Czock; Matthew A. Levin; Johannes Wieditz; Leif Saager; Konrad Meissner; Onnen Moerer (PLoS ONE, 2025)
Background The concept of ventilating multiple patients concurrently using a single ventilator has been proposed as a solution when the demand for ventilators surpasses the available supply. While the practicality of this approach has been established, a thorough evaluation of the risks involved has yet to be comprehensively addressed. Methods Two circuits, a simple one (circuit-1) and another with an adjustable resistance valve (circuit-2), were evaluated within an experimental framework utilizing two computer-controlled lung simulators (TestChest and ASL 5000). These simulators were ventilated by an ICU (intensive care unit) ventilator (Servo-u) employing various ventilation modes (volume- and pressure-controlled ventilation). The study was conducted under differing respiratory conditions, characterized by low compliance (20 ml/cmH2O) as well as normal-high compliance (100 ml/cmH2O), in order to ascertain the applied tidal volume (VT), pressures, and the resultant mechanical power (MP). Results Circuit-1: The applied VT, pressures, and MP differed significantly between the two simulators, as well as in relation to ventilation mode, compliance, and respiratory rate (RR) (p < 0.001); the differences were most pronounced in settings with differing compliance levels. Circuit-2: Differences in VT, pressures, and MP were observed between simulators concerning valve settings (p < 0.001). The VT demonstrated a negative correlation, with volumes derived from valve closure spanning from 50 to 100 ml across all settings. In the design of circuit-2, MP exceeded the 12 J/min threshold in both lung simulators at elevated RR and could only be decreased through valve closure followed by a consequential hypoventilation in one simulator. Conclusion The simultaneous ventilation of two patients using a single ventilator is technically viable, yet it presents considerable risks. Even with the integration of an adjustable resistance valve to accommodate varying lung complexities, the likelihood of unilateral hypoventilation and elevated mechanical stress remains high.